OPTIMALISASI PLATFORM DIGITAL SEBAGAI SARANA PEMASARAN UMKM DI DESA BANJARSARI - Cahyadi, Ujang; Wandani, Anggi; Hidayatullah, Irfan; Maulana, Helmi; Berliana, Lyan; Rahmi, Murni Lestari; Nurapipah, Nisa; Saputra, Rizki; Apriansyah, Randi; Safari, Muhamad Ikhsan; Shudur, Syifaus; Safitri, Andriani; Muti, Muhammad Hafash Al; Fauziah, Fitria Nurhaliza; Muhaemin, Algi; Ramadhan, Adam Putra; Hakim, Muhammad Luqmanul; Imanulloh, Agil Nazhar; Zirzis, Yogie Wahyudin; Daud, Ridwan Muhammad; Nasrullah, M. Nabil Naufal (Institut Teknologi Garut, 2024)
In the current digital era, the emergence of technology and high business competition makes MSMEs compete with their competitors. Conventional marketing strategies are no longer enough to win the competition. Unfortunately, there are still many MSMEs that have not been able to optimize digital platforms as a marketing tool, especially MSMEs in Banjarsari Village. Therefore, Group 3 KKN students prepared a work program for Micro, Small and Medium Enterprise Development in Banjarsari Village. The aim is to provide assistance and assistance as well as understanding the importance of digital marketing to expand market reach. The results achieved are that MSMEs in Banjarsari Village have an Online Shop as a means of marketing products online and facilitating communication and transactions with consumers.